The Levels of Factor XIIa Generated in Human Plasma on an Electronegative Surface Are Insensitive to Wide Variation in the Concentration of FXII, Prekallikrein, High Molecular Weight Kininogen or FXI - Mitropoulos, K. A. (Thrombosis and Haemostasis, 1999)
The contribution of the various components of the contact system in the generation of factor XIIa (FXIIa) and of kallikrein (KRN) on an electronegative surface and the release of the generated enzymes to the bulk phase was examined in mixtures of normal human plasma and plasmas congenitally deficient in these components. The incubation of normal human plasma in the presence of sulphatide vesicles (40 μM) resulted in a fast generation of amidolytic activities due to FXIIa and to KRN followed by slower first-order inactivation rates of FXIIa (k’FXIIa) and of KRN (k’KRN) due to the presence of esterase inhibitors. Variation of the levels of factor XII (FXII), over a wide range, showed little effect on levels of FXIIa and of KRN but no activities were detected in 100% FXII-deficient plasma. The variation of prekallikrein (PKRN) concentration showed little effect on the generation of FXIIa but the generation of KRN declined linearly with the decrease in the level of PKRN. No activities were detected on treatment of PKRN-deficient plasma. The variation in the concentration of high molecular weight kininogen (HK) showed effects on FXIIa and KRN that were qualitatively similar to those seen on variation of PKRN but 100% HK-deficient plasma generated considerable activities of both FXIIa and KRN. The variation in the concentration of factor XI (FXI) showed no effect on the generation of FXIIa, whereas KRN levels increased linearly with the contribution of FXI-deficient in normal plasma. The present results suggest that the contiguous binding of FXIIa, FXII, PKRN-HK and FXI-HK onto the electronegative surface induces a rapid generation of FXIIa and KRN. The bound PKRN-HK complex prevents the release of generated FXIIa and therefore further binding and activation of FXII from the bulk phase. Consequently, the turnover of FXII is independent of its levels in the bulk phase and is rather related to the concentration of contact surface. The generated KRN is also protected by HK. However, since the enzyme responsible for the activation of PKRN-HK is FXIIa, the levels of generated KRN are positively related to the concentration of substrate.
Keywords: Contact activation; factor XII; prekallikrein; high molecular weight kininogen; regulation of activation